Niobium-based oxides for oxidative and reductive photocatalytic reactions - Oliveira, Jéssica Ariane de (2020)
It is growing the number of studies related to alternative technologies allowing both, environmental remediation and clean energy production. In this sense, photocatalysis is a promising process, since it is sustainable and operated under ambient conditions. Niobium pentoxide (Nb2O5) is one of the most promising semiconductors for photocatalytic reactions due to its chemical and physical stability, non-toxicity, versatility, and excellent photoactivity. Considering that (i) photocatalysis is an emerging research field, mainly for energy storage in chemical bonds, and (ii) Brazil has the world`s largest niobium reserves; it is of paramount importance the improvement of niobium properties in order to obtain a valuable product. Thus, the main objective of this thesis is developing strategies to (i) increase the absorption spectrum of Nb2O5 for the visible region, since it is activated only by ultraviolet illumination, and (ii) decrease the recombination rate of the photogenerated charges because it is a factor that directly influences the photocatalytic efficiency. Doping is a suitable option to decrease the band gap of semiconductors because the doping atoms create impurity levels (IL) between the VB and CB, leading to radiations with lower energy to promote an electron from the VB to the IL than from the VB to the CB. Then, the material initially excited only under ultraviolet radiation, can also become active under visible light. In this sense, zinc was chosen as dopant due to its abundance, low-cost, and ionic radius and electronegativity similar to that of Nb5+ that leads to an effective insertion into the Nb2O5 crystalline structure. The synthesized samples showed remarkable activities in the photooxidation of rhodamine B and caffeic acid, under visible radiation, even after consecutive cycles. The results have been correlated to the low concentrations of zinc (0.1 and 0.2 mol%) that were enough to ensure that all particles had at least one doping atom for decreasing the electron excitation energy, but, at same time, the impurities were not in excess to guarantee that the dopants were not acting as recombination centers. Another modification is the formation of a Z-scheme between Nb2O5 and basic bismuth nitrates (BBN). BBN are easily synthesized and have been identified as promising photocatalysts, but their properties in reduction reactions has not been explored yet. The nanocomposites exhibited notable photoresponse for the selective conversion of CO2 to CO and C2H4, mainly due to the band edge positions of the isolated semiconductors that led to a special separation of the photogenerated charges, consequently, molecules were oxidized on the Nb2O5 VB, while CO2 was reduced on the BBN CB. Considering that low-cost materials (Zn and BBN) have been successfully employed to modify Nb2O5 by hydrothermal treatment, a simple method to obtain semiconductors at low temperature, and based on the photocatalytic properties of the as-synthetized photocatalysts, it can be concluded that the Nb2O5-based materials developed in this work have potential to be used for large scale in applications for both, reductive and oxidative reactions.